Process-orientated learning as key aspect in handling uncertainty. experimental teaching methods in continuing education in spatial planning - Grams, Anita (AESOP, 2017)
Understanding spatial planning as an action-oriented discipline allows planning to concern itself with the exploration, clarification, and resolution of difficult, unsolved tasks. The starting points for this are both spatially relevant conflicts and desirable spatial developments, as the latter too can likewise lead to future difficult and unsolved tasks. Due to the fact that solutions to spatial planning problems always lie in the long- term future, clarification processes must be able to adroitly handle circumstantial changes linked to uncertainties, such as changing political priorities or shrinking financial resources. Employing model calculations and perfecting forecasting methods alone is insufficient for appropriately dealing with the degree of uncertainty in a planning process. On the contrary, what is needed are methods that take into account the uncertainties, as well as desired and undesired effects of decisions in solution-finding processes. A universally valid approach for exploring, clarifying, and solving future spatially relevant problems cannot be prescribed; this depends on the given tasks, and must be tailored to the respective problem situation (SCHOLL 2011: 279). Moreover, what underlies most difficult, unsolved tasks is a decision-making problem (BEHN/VAUPEL 1982: 40 f.), which in turn triggers subsequent action. As such, approaches for laying the groundwork for decision-making and actions take centre-stage in research and teaching on spatial planning.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017